THE PREVALENCE OF UNHEALTHY SNACKING BEHAVIOUR AND ITS ASSOCIATION WITH INDIVIDUAL AND ENVIRONMENTAL FACTORS AMONG COLLEGE STUDENTS IN KUCHING, SARAWAK - Yong Xiang, Cheah; Whye Lian, Cheah (UKM, 2021)
Unhealthy snacking behaviour among young people is a growing public health concern because of its negative consequences on health. This study was to determine the prevalence of unhealthy snacking behaviour and its determinants among college students in Kuching. In this cross-sectional study, 12 colleges in Kuching were stratified into private and government colleges. Three private and three government colleges were selected through a stratified random sampling method. A total of 422 respondents (male 49.5%, female 50.5%) were recruited in this study. A self-administered questionnaire was used to gather data regarding unhealthy snacking behaviour and its determinants (gender, food preferences, type of school and courses, taste-and-sensory perception, nutritional knowledge, perceived self-efficacy, and cost/price sensitivity, perceived parental control, easy accessibility, and media advertisements influence) among respondents. The survey was conducted online via e-mail/Whatsapp. Multiple binary logistic regression analysis was used to analyse the data. A quarter of the respondents (24.6%) practised unhealthy snacking behaviour. More than half of the respondents (58.3%) consumed unhealthy snacks one to three times per week. A minority of the respondents (17.1%) claimed that they did not consume any unhealthy snacks for the past month. The final model explained 15.7% of the total variance. Taste-and-sensory perception (Adjusted OR = 2.20, 95%CI [1.55, 3.13], p < 0.001) and nutritional knowledge (Adjusted OR = 1.48, 95%CI [1.12, 1.97), p < 0.05) were positively associated with unhealthy snacking behaviour among respondents. The present study suggested the stakeholders concentrate on nutritional knowledge and taste-and-sensory perception among college students in future intervention development